Santiago's children : what I learned about life at an orphanage in Chile - Reifenberg, Steve, 1959- (University of Texas Press, 2008)
Unclear about his future career path, Steve Reifenberg found himself in the early 1980's working at a small orphanage in a poor neighborhood in Santiago, Chile, where a determined single woman was trying to create a stable home for a dozen or so children who had been abandoned or abused. With little more than good intentions and very limited Spanish, the 23 year-old Reifenberg plunged into the life of the Hogar Domingo Savio, becoming a foster father to kids who stretched his capacities for compassion and understanding in ways he never could have imagined back in the United States.